Islamization of human knowledge: an overview of the concept, scope and method - Junaid, Muhammad; Ali, Mohd Mumtaz (IIUM Press, International Islamic University Malaysia, 2017)
This study aims to analyse the concept of IOHK based on various definitions presented by scholars. Using analytical and critical approaches, the study examines these definitions and highlights the extended scope, objectives and methodology of IOHK. It also evaluates the works of its proponents and opponents on the different perspectives. In addition, this study attempts to analyze the possible use of the term ‘relevantization’ for Islamic sciences which are named Islamic Revealed Knowledge Disciplines (IRKDs) in IIUM